Anaphylactic reaction to ingestion of Quercus ilex acorn nut (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.

Anaphylactic reaction to ingestion of Quercus ilex acorn nut - Vega; DomÍnguez; Cosmes; MartÍnez; BartolomÉ, B.; Palacios; Vega, a; Domínguez, C.; Cosmes, P.; Martínez, a; BartolomÉ, B.; Martínez, J.; et al. (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd, UK accession-num: 9677139
Keywords: acorn allergens; Anaphylaxis; Anaphylaxis: drug therapy; Anaphylaxis: etiology; Bet v 1; Cross Reactions; Electrophoresis; Food Hypersensitivity; Food Hypersensitivity: drug therapy; Food Hypersensitivity: etiology; Humans; Immunoblotting; Immunoglobulin E; Immunoglobulin E: blood; Male; Middle Aged; nut allergy; Nuts; Nuts: adverse effects; Nuts: immunology; Polyacrylamide Gel; Quercus ilex allergy; Radioallergosorbent Test; Skin Tests

Assessment of sensitization to holm oak (Quercus ilex) pollen in the Mérida area (Spain) (Allergy, 1995)
Sensitization to Quercus ilex(holm oak) was studied in 760 patients with clinical suspected sensitization to aeroallergens. Prick tests with commercial extracts of Q. ilex proved positive in 27 patients; none were monosonsitive. Nasal and conjunctival provocation tests and specific IgE (RAST) performed with Q. ilex extracts in these patients were negative in all hut one patient, who exhibited specific IgE: liter by RAST) of 7 PRU ml (class 3). We conclude that Q. ilex pollen, though obtained in considerable quantities by our collector, docs not cause allergies in our area.

Resultado de los estudios regionales de introducción y adaptación de especies y variedades pascícolas en zonas semiáridas del SW español (Pastos, 1977)
Results from a series of triáis conducced in S.W. Spain between 1972-1976 using different species and varieties of grasses and legumes indicated the advantages from fertilizer applications in all the áreas studied with the exceptions of "La Serena" and "Palomas-Hornachos". Soil deph was also a major factor determining the success of pasture establishment and subsequently persistence and production. The Australian subclover cultivare used in these triáis did not generally persist adequately. It is tberefore concluded that there is a need to select "local" ecotypes of this species and of others species that are more adapted to the environmental conditions of the zone. More information is also required on the environmental factors, managerial practicas and agro- nomic characteristics that contribute to persistence of annual legumes. It is believed that persistence is the major determinant of success in pasture improvement involving the use of annual legumes; with perennial grasses in S.W. Spain, establishment appears to be major determinant. 222